PEMANFAATAN INSTAGRAM SEBAGAI SOCIAL MEDIA MARKETING ER-CORNER BOUTIQUE DALAM MEMBANGUN BRAND AWARENESS DI KOTA PEKANBARU - Fauzi, Viny Putri; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study discusses the use of instagram as social media marketing to build brand awareness Er-corner Boutique in Pekanbaru. The research aims to know the use instagram in increasing knowledge of consumers who are not aware of the brand (brand Unware), to establish the level of brand recognition, to know the level of brand recall, and to know how the top of mind consumer Er-corner boutique in Pekanbaru.In this study the authors used a qualitative descriptive study with data collection techniques through observation, interviews and documentation. Informants in this study were 8 people who were taken by purposive sampling technique, those are Er-corner boutique owner, 2 employees Er-corner boutique, and 5-corner Er customers who use instagram. Interactive data analysis models the researchers use to describe the results of research into techniques for data analysis and data validity checking researcher use triangulation techniques.The results showed that the use instagram by Er-corner boutique Pekanbaru in building its brand awareness of Unware of the brand is paid promote, endorsement selebgram, and posted a photo of outfit of the day (ootd) done by the owner Er-corner. After that strategies to increase brand recognition in instagram used by Er-corner boutique is intense sharing photos of products, positive testimonials from customers and provide promo discounts and held several quizzes with prizes. Tactics conducted by Er-corner boutique in making the brand recall to the consumer by providing information about fashion and give quizzes with prizes to consumers every month twice and intense posting photographs of Er-corner boutique products every day. While the top of mind that Er-corner boutique get is increasing followers Er-corner for more than two years have followers on instagram more than 3500 (without follow customer first, it means pure of followers) and has more than 500 testimonies positive for years 2014-2015.Keyword: Utilization Instagram, Social Media Marketing, Brand Awareness